THE EFFECT OF STUNTING ON COGNITIVE AND MOTOR DEVELOPMENT IN TODDLER CHILDREN : LITERATURE REVIEW - Eva Supriatin; Diwa Agus Sudrajat; Firda Annisa R; Linlin Lindayani (Jurnal Ilmu Keperawatan Anak, 2020)
Stunting is a condition in which toddlers have less length or height compared to age. Stunting can affect physical growth, motor development, and motor activity. Children who experience motor skills are caused by obstacles to the muscle maturity process so that muscle ability is reduced. Many studies say there is a link between cognitive and motor development. Objective: To study the effect of stunting against cognitive and motor development in children toddlers. This study is a systematic review of the literature. The inclusion criteria for search studies were quantitative research, free full text, Indonesian, or English. Selection of published articles with a range of 2015-2020 and free full text, after reading the title of the article and looking at the inclusion criteria, then it is re-selected by looking at the sample criteria based on age and development, and an assessment is carried out using the JBI format. There is a stunning effect on the cognitive and motor development of children ages toddler. The results of the study stated that children who were stunted had an 11.98 times greater chance of having motor development below average. As well as the mild stunting category with cognitive development suspect there is a delay in toddlers, namely not being able to mention the type of color, differentiating the size of the object, mentioning gender, pairing known images. While the moderate stunting category with cognitive development suspect or experiencing delays can result in reduced brain cells by 15-20 percent. Toddlers who experience the severe stunting category with cognitive development suspect there is a delay, marked by slow maturity of nerve cells, slow motor movements, lack of intelligence, and slow social response. Stunting affects cognitive and motor development in children toddlers. Some of the impacts that arise are memory decline, inaccuracy in storing objects, delays in verbal and non-verbal, and delays in thinking.